Membandingkan Akurasi Financial Distress Berbasis Model Peramalan Kebangkrutan - Langgeng Prasetyo Utomo (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2020)
This study aims to determine the differences between the Altman Model, the Zmijewski Model, the Springate Model and the Grover Model in predicting bankruptcy in companies that experienced losses in a row from 2013 to 2018. In this study, the sample technique used was purposive sampling by taking 24 samples of companies that suffered losses for two years in a row in the observation year were obtained. The analysis method used is One Way Anova. The results of this study indicate that the Altman Model, the Zmijewski Model, the Springate Model and the Grover Model differ in predicting company bankruptcy. Based on the Post-Hoc test and manual accuracy calculation shows that among the four models in this study